Nuclear Village and Risk Construction in Japan: A Lesson Learned for Indonesia - Sarjiati, Upik (Journal of Indonesian Social Sciences and Humanities, 2015)
Japan’s success in the development of nuclear energy cannot be separated from the role of the ‘nuclear village’, a pro-nuclear group comprising experts, bureaucrats, politicians and the mass media. The nuclear village created an image of nuclear energy as ‘safe, cheap and reliable’. Using this nuclear village was one of the strategies used to construct a perception of the risk of nuclear energy. Thus, the acceptance by Japanese people of nuclear energy is an important factor in their support for economic development. However, the Fukushima nuclear accident changed the public’s perception of nuclear energy and the Japanese Government was asked to end the operation of nuclear power plants. The government decided to change energy policy by phasing out nuclear power by the end of year 2030. Conversely, the Fukushima nuclear accident has not impeded the Indonesian Government’s plans to build nuclear power plants. Thus, understanding how the Japanese Government managed nuclear risk is expected to raise Indonesian public awareness of such risks.